2019
DOI: 10.14359/51718008
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Testing of Nonductile Reinforced Concrete Wall Boundary Elements

Abstract: interests include the design and experimental assessment of RC walls and the collapse behaviour of non-ductile RC buildings in lower seismic regions. ABSTRACT This paper presents an overview and results of a recent experimental testing program of nonductile reinforced concrete (RC) wall boundary elements. The experimental program consisted of seventeen boundary element prism specimens that are meant to represent the end regions of non-ductile RC walls. The failure mechanisms of interest were global out-of-plan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 18 publications
1
1
0
Order By: Relevance
“…The rebar buckling in specimen TUE is comparable to the mode of failure observed in specimen P10 from Menegon et al (2019), as shown in Figure 8c. Several boundary element prisms, representative of end regions of non-ductile RC walls, were tested by Menegon et al (2019) under cyclic uniaxial tension-compression, with specimen P10 having a thickness of 130 mm and detailed with a central layer of three vertical reinforcing bars of 16 mm diameter, characteristics that are strikingly similar to the boundary ends of the flanges of TUE (and TUF).…”
Section: Tue Observationssupporting
confidence: 62%
See 1 more Smart Citation
“…The rebar buckling in specimen TUE is comparable to the mode of failure observed in specimen P10 from Menegon et al (2019), as shown in Figure 8c. Several boundary element prisms, representative of end regions of non-ductile RC walls, were tested by Menegon et al (2019) under cyclic uniaxial tension-compression, with specimen P10 having a thickness of 130 mm and detailed with a central layer of three vertical reinforcing bars of 16 mm diameter, characteristics that are strikingly similar to the boundary ends of the flanges of TUE (and TUF).…”
Section: Tue Observationssupporting
confidence: 62%
“…Several boundary element prisms, representative of end regions of non-ductile RC walls, were tested by Menegon et al (2019) under cyclic uniaxial tension-compression, with specimen P10 having a thickness of 130 mm and detailed with a central layer of three vertical reinforcing bars of 16 mm diameter, characteristics that are strikingly similar to the boundary ends of the flanges of TUE (and TUF). The authors note that the bar buckling in P10 initiated at a lower tension strain due to the vertical splitting of the specimen, which indicated 'that local bar buckling is potentially worse in singularly reinforced walls' (Menegon et al, 2019) in comparison to walls with two layers of vertical reinforcement primarily because of the absence of stirrups or crossties in singularly reinforced walls. The rebar buckling in TUE can also be compared to specimen TUC, tested by Constantin and Beyer (2016).…”
Section: Tue Observationsmentioning
confidence: 99%